Perfil hematológico de cães (canis lupus familiaris) soropositivos para leishmania spp atendidos no hospital veterinário de uberaba – mg - Lacerda, Moacir Santos de; Sampaio, Renato Linhares; Rezende, Rodrigo Supranzetti; Gomes, Antoniete Lourenia (2017)
The aim of the study was to characterize the hematological profile of dogs seropositive for Leishmania spp at the Veterinary Hospital of Uberaba – MG, Brazil. Samples were collected from 15 seropositive dogs and analyzed using indirect immunofluorescence tests and enzyme-linked immunosorbent assay (ELISA) for hematological analysis. Out of the 15 dogs, 12 (80%) were female, 9 (53.33%) were more than 8 years of age, and 6 animals (40%) were mongrels, which was the predominant breed. The most frequent finding was anemia (53.3%; n = 8). Further, out of 15 animals, 6 (75%) presented with normocytic-normochromic anemia, while the plasma total protein levels were increased in 8 (53.33%). Analysis of the white blood cells revealed that 3 (20%) dogs had leucopenia and 2 (13.3%) had leukocytosis. Leukocyte differential analysis revealed that 3 (20%) animals had neutrophilia, 2 (13.33%) had neutropenia, left drift was observed in 3 (20%), monocytosis in 1 (0.66%), eosinopenia in 8 (53.33%), and lymphopenia in 3 (20%). The results of this study reveal that anemia, hyperproteinemia, and eosinopenia in seropositive animals are indicative of canine visceral leishmaniasis (CVL). Therefore, the hematologic profiles obtained from animal studies aid in the diagnosis of CVL. O objetivo deste trabalho foi caracterizar o perfil hematológico de cães reagentes para Leishmania spp atendidos no Hospital Veterinário de Uberaba – MG. Foram coletadas amostras de sangue de 15 cães sororreagentes nos testes de Imunofluorescência Indireta e ELISA para realização do hemograma. Dos quinze cães, 12 (80%) eram fêmeas, 53,33% (n=9) tinha idade acima de 8 anos, enquanto que a raça de maior prevalência foi a sem raça definida com 6 animais (40%). O achado mais frequente no eritrograma foi a anemia (53,3%) (n=8). Destes animais, 75% (n=6) apresentaram anemia normocítica-normocrômica. Os níveis plasmáticos de proteínas totais estavam aumentados em 8 dos 15 (53,33%) cães. A leucometria mostra que 03 (20%) cães apresentaram leucopenia e 02 (13,3%), ...